Analysis of the Level of Consumer Satisfaction with the Attributes of Kuansing Batik Products in Taluk Kuantan City - Aidil Febrian; Jushermi Jushermi; Aida Nursanti (West Science Business and Management, 2026)
This study aims to analyze consumer satisfaction levels regarding the product attributes of Batik Kuansing in Taluk Kuantan City and to formulate strategies for improving consumer satisfaction. The method used in this study is Importance Performance Analysis (IPA) with a quantitative approach. Primary data was collected through questionnaires distributed to 102 respondents who had used Batik Kuansing products in the past three months. The analyzed variables include product attributes such as price, color variety, design/motif, craftsmanship quality, and raw material quality. The results show that most consumers are satisfied with the attributes of Batik Kuansing products; however, certain aspects such as price and craftsmanship require improvement. The recommended strategy to enhance consumer satisfaction is the implementation of Relationship Marketing and Management to strengthen customer relationships and foster loyalty. This study is expected to serve as a reference for Batik Kuansing artisans and business actors in sustainably improving their product quality.